Assessment Wine Aroma Persistence by Using an in Vivo PTR-ToF-MS Approach and Its Relationship with Salivary Parameters - Muñoz-González, Carolina (Molecules, 2019)
To better understand wine aroma persistence, the nasal cavity of nine volunteers was monitored by Proton Transfer Reaction-Time of Flight-Mass Spectrometry (PTR-ToF-MS) after they rinsed their mouths with three rosé wines (one control and the same wine supplemented with two tannin extracts) during four minutes. Wines were aromatised with a mixture of five target aroma compounds. Results showed that wine aroma persistence was highly compound-dependent: while esters disappeared very fast, other compounds such as linalool remained in the oral cavity for longer times after wine expectoration. A low effect of tannins (at 50 mg/L) on nasal cavity parameters was observed, with the exception for the compound ethyl decanoate that was significantly higher released in the presence of tannins. Strong interindividual differences on aroma persistence were also found. Significant positive correlations with the salivary total protein content and negative with the salivary flow were observed for specific compounds. This work has studied for the first time in vivo wine aroma persistence in real time from an analytical perspective.